2021
DOI: 10.1111/bjh.17977
|View full text |Cite
|
Sign up to set email alerts
|

Significance of anti‐HBc serological status in primary immune thrombocytopenia

Abstract: The association of previous hepatitis B virus (HBV) exposure [hepatitis B surface antigen (HBsAg) negative, hepatitis B core antibody (anti-HBc/HBcAb) positive] with disease severity and decision on treatment option in primary immune thrombocytopenia (ITP) patients remains unclear. Data from 725 patients diagnosed with ITP were analyzed to elucidate the association between anti-HBc serological status and disease severity. Data from a published prospective study [high-dose dexamethasone (HD-DXM), HD-DXM plus r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our previous studies showed that HPV infection was signi cantly associated with ESCC [8], and the expression of P53 is positively correlated with miR-34a in ESCC cells [50]. In this study, we found that the mRNA level of P53 and miR-34a had signi cantly decreased in HPV-infected Ec109 and Ec9706 cell lines, which demonstrated that the expression of p53 and miR-34a may be also closely related in HPV-infected ESCC cells.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Our previous studies showed that HPV infection was signi cantly associated with ESCC [8], and the expression of P53 is positively correlated with miR-34a in ESCC cells [50]. In this study, we found that the mRNA level of P53 and miR-34a had signi cantly decreased in HPV-infected Ec109 and Ec9706 cell lines, which demonstrated that the expression of p53 and miR-34a may be also closely related in HPV-infected ESCC cells.…”
Section: Discussionsupporting
confidence: 63%
“…EAC is the major histological type of esophageal cancer in the western countries, while the incidence of ESCC is particularly common in Asia, especially in China [3,4]. EAC is closely associated with gastroesophageal re ux [5], And a number of studies have reported that HPV infection might be one of the potential risk factor of ESCC [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, patients who tested positive for HBV 94.8% had no response. In patients with ITP, HBV exposure was found to be associated with greater disease severity and hospitalization rates 57 , and may be considered a predictor for poor response to ITP-specific treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, viral hepatitis infections, specifically hepatitis B and C, have been associated with immune thrombocytopenia (ITP) through various mechanisms, including molecular mimicry, epitope spreading, and immune dysregulation [ 14 ]. Interestingly, patients with hepatitis C virus (HCV) or hepatitis B virus (HBV) have a higher likelihood of being infected with Helicobacter pylori compared to individuals with autoimmune liver cirrhosis (ALC) or primary biliary cirrhosis [ 14 , 15 ]. A study by Salehi et al (2014) revealed that patients who underwent H. pylori eradication regimens experienced reduced liver enzyme levels.…”
Section: Introductionmentioning
confidence: 99%